Molecular Docking Analysis of Zerumbone Derivatives as XIAP-BIR3 Inhibitor for Anticancer Agent - Winni Nur Auli; Nisa Yulianti Suprahman; Riri Fauziyya; Sarmoko; Arif Ashari; Safia Fazila; Qurrota A`yun Azzahrah; Romualdo Pasaribu; Putri Liswatini; Ihza Adzkiya Mubarak Al-Husni; Dinda Naila Dhiya Salsabila (Future Science, 2024)
Cancer is the second most common cause of death worldwide. Common therapies used to treat cancer include radiation, chemotherapy, and surgery. However, resistance to treatment often gives a challenging problem, and new alternative therapies derived from natural compounds are needed. Zerumbone is terpenoid compound with various biological activities, including anti-tumor and anti-cancer. This study aims to investigate the activity of Zerumbone and its derivatives against the XIAP-BIR3 protein. The target protein used PDB ID: 4KMP as inhibitor of XIAP-BIR3. There are 21 zerumbon derivatives retrieved from published article. Docking of zerumbone derivatives was performed using Autodock 1.5.6. Molecular docking result showed derivative 6 of Zerumbone has potential as an anti-cancer agent with a binding energy of -7.84 kcal/mol; meanwhile, the reference inhibitor has a binding energy of -5.21 kcal/mol. These results of the study indicate that the development of inhibitor XIAP-BIR3 may be a potential strategy in cancer treatment and zerumbone derivatives are predicted to be potential candidates that can be analyzed further.